Quantification of nutrient uptake and allocation under phosphate stress in rice using ionomics techniques - Pandey, Priyanka (2017)
The rampant use of phosphate fertilizers, a non-renewable resource with limited supply, for increasing crop productivity is beset with problems linked to human health and environment. With the use of biotechnology, development of varieties with high phosphate (Pi) uptake efficiency and utilization capabilities is possible but it requires thorough understanding of physiological mechanisms regulating phosphate stress. Ionomic profile of the tissue undergoing phosphate stress can be of use to understand physiology of stress response. In this experiment effects of hydroponic solutions with low or high concentration of Pi on plants were studied on Oryza sativa ssp japonica cultivar Nipponbare for 21 days. Rates of nutrient uptake by the whole plant from hydroponic solutions with different Pi treatments and their allocation to shoot and root tissues were calculated by using ionomic profiles of hydroponic solutions and shoot/root tissues over a period of 21 days. The plants were initially grown on hydroponic solutions with 320 µM Pi for 15 days before being subjected to different Pi treatments. Stunted shoots with reduced uptake as well as allocation of potassium and phosphorus to shoot and increased allocation of molybdenum and copper to roots were markers of Pi stress in Nipponbare. Ionomic profiles of macronutrients revealed opposite allocation patterns in shoot and root tissues during Pi stress. Study of marker elements for Pi stress in rice is done for the first time. Judicious use of phosphate fertilizers and addition of required nutrients to crop lands can be planned based on study of ionomic profile of crop plants to obtain their optimum production and mitigate problems related to overuse of phosphate fertilizers.